Avaliação de aplicação de um modelo de governança de TI verde em uma universidade pública - Cavet, Guilherme Rodrigues (2024)
The objective of this present dissertation is to evaluate the application of a green IT governance model in a public university. The justify of the study is the importance of monitoring IT practices with the principles of sustainability and environmental responsibility in universities. The research is qualitative and exploratory in a case study, with a triangulation of data from diverse sources, which contributes to the methodological robustness of the study and to obtaining informed conclusions. The research results reveal the identification of forty-five Green IT practices and concepts conducted at the university under study and, with the systematic review, in other scientific universities, highlighting the importance of considering different motivational and pressure factors to promote sustainability in information technology operations. The study highlights the relevance of updating the technological advancement of higher education institutions with sustainability, evolving a more responsible and ecologically conscious IT management. It also highlights the need to motivate management and internal stakeholders of universities to adopt Green IT practices, as well as the importance of external pressures, such as legislation and regulations, in promoting sustainability. Furthermore, the application of governance models stands out, such as the green technology information governance and management framework (GMGIT), to guide the university under study on the path to sustainability in the IT area. Furthermore, the study contributes to raising awareness about the importance of environmental and social sustainability in the academic context and highlights the need to continue investigating and implementing sustainable practices, to promote a greener university environment aligned with the principles of sustainability. Finally, future research aims to continue the development and implementation of Green IT practices in universities and generate a positive impact on the environment and society.